2001
DOI: 10.3168/jds.s0022-0302(01)74695-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Nonforage Diet on Milk Production, Energy, and Nitrogen Metabolism in Dairy Goats throughout Lactation

Abstract: The objective of the experiment was to compare a silage-based control diet (C) with a nonforage diet (NF) in dairy goats throughout lactation in terms of animal performance and energy utilization. Eight Saanen goats were divided into two groups and fed C or NF, a commercial blend that included sunflower meal, cassava, coconut meal, and whole cottonseeds as the main ingredients that was characterized by a small particle size and a high crude protein content. In early, mid, and late lactation (44, 100, and 219 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
36
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 15 publications
11
36
1
4
Order By: Relevance
“…This test measured the total degree of linear relationship between BCS and daily milk yield within each level, despite of the individual stage of lactation. Means of milk urea were similar to those by Bava et al (2001) for Saanen goats, with higher milk yield and lower milk protein content. However, the present data were lower than those by Sahoo & Walli (2008) for crossbred goats and by Cabiddu et al (1999) for Corsican goats fed exclusively pasture.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This test measured the total degree of linear relationship between BCS and daily milk yield within each level, despite of the individual stage of lactation. Means of milk urea were similar to those by Bava et al (2001) for Saanen goats, with higher milk yield and lower milk protein content. However, the present data were lower than those by Sahoo & Walli (2008) for crossbred goats and by Cabiddu et al (1999) for Corsican goats fed exclusively pasture.…”
Section: Discussionmentioning
confidence: 49%
“…Indeed, protein can be produced in the rumen from urea and other nitrogen sources and the flow of urea is from the rumen to the blood and vice versa (Harmeyer & Martens 1980, Cunningham 2002. Plasma urea is positively correlated to milk urea in cows (Roseler et al 1993, Butler et al 1996, Broderick & Clayton 1997, sheep (Cannas et al 1998) and goats (Cabiddu et al 1999, Bava et al 2001, Sahoo & Walli 2008. Given that milk is easier to collect than blood, milk urea is a suitable parameter to evaluate urea metabolism, especially on a herd level (Schepers & Meijer 1998), both in intensive and extensive dairy farms.…”
Section: Introductionmentioning
confidence: 99%
“…However Bava et al (2001) reported higher levels of urea in milk than in plasma, but also a positive correlation between these values. The content of ammonia in rumen fluid (Table 4) differed highly between the diets (P<0.01).…”
Section: Resultsmentioning
confidence: 97%
“…However, studying diets without forages in goat feeding, Bava et al (2001) observed lower digestibility coefficients for the diets containing the highest levels of forage. These authors attributed this effect of the digestibility coefficient to a higher passage rate of the diets without forages, i.e., with a higher amount of easily-fermentable carbohydrates (concentrate).…”
Section: Resultsmentioning
confidence: 99%